Bridging the gap between a set of interrelated business process models and software models - Cruz, Estrela (2015)
A business process model identifies the activities, resources and data involved in the creation of a product or service, having lots of useful information for starting to develop a supporting software system. With regard to software development, one of the most difficult and crucial activities is the identification of system functional requirements. A popular way to capture and describe those requirements is through UML use case models. Usually an organization deals with several business processes. As a consequence, a software product does not usually support only one business process, but rather a set of business processes. This paper presents an approach that allows aggregating in one use case model all the information that can be extracted from the set of business process models that will be supported by the software under development. The generated use case model serves as a basis for the software development process, helping reducing time and effort spent in requirements elicitation. The approach also helps to ensure the alignment between business and software, and enables traceability between business processes and the corresponding elements in software models.